Encyclopedia of Structural Health Monitoring 2008
DOI: 10.1002/9780470061626.shm079
|View full text |Cite
|
Sign up to set email alerts
|

Global Navigation Satellite Systems (GNSSs) for Monitoring Long Suspension Bridges

Abstract: Global navigation satellite system (GNSS), notably global positioning system (GPS), has been utilized for more than a decade in the deformation monitoring of a variety of stationary structures such as dams, building, slopes, etc., around the world. With the technological advent of GPS positioning, telecommunications, and signal processing, as well as public awareness, GPS has been widely used in recent years for monitoring slender structures such as large suspension bridges and high‐rise buildings. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Special attention is being paid to the newly introduced GNSS monitoring system because of limited experience and versatility. Along with information about general displacements and movements of the bridge, previous studies on GNSS-based monitoring showed that dynamic responses of the bridges could be obtained (10). To assess the viability of the GNSS for deriving dynamic properties of the Seohae Bridge, natural frequencies were extracted by using sample data from the GNSS receivers and accelerometers.…”
Section: Initial Findingsmentioning
confidence: 99%
“…Special attention is being paid to the newly introduced GNSS monitoring system because of limited experience and versatility. Along with information about general displacements and movements of the bridge, previous studies on GNSS-based monitoring showed that dynamic responses of the bridges could be obtained (10). To assess the viability of the GNSS for deriving dynamic properties of the Seohae Bridge, natural frequencies were extracted by using sample data from the GNSS receivers and accelerometers.…”
Section: Initial Findingsmentioning
confidence: 99%